A REVIEW OF ROAD TRAFFIC HAZARD AND RISK ANALYSIS ASSESSMENT - Leon Luiz Lakim; Nabila Abdul Ghani (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Few studies have stressed on the interrelating between the categories which will show the level of road risk and hazard more efficiently. The relatively of risk were interrelating with the road hazard. Therefore, the objective of this paper is to identify the direction of study of road traffic hazard and risk analysis throughout the year 1977 to 2020. Review works of literature were identified through multiple sources from transport planning and transport engineering database available in open access journals with a focus on keywords of ‘road risk analysis and hazard’ and road risk assessment. The review showed that while previous research focused on qualitative and quantitative risk analysis in order to get risk rate accuracy was less accurate. The risk analysis and hazard taken a few changes it has been improvised a few times in order to get more accurate risk rate and data which will help to improve road safety.